Correction: Mass-shift mode to quantify low level 129I in environmental samples by ICP-MS/MS. Issue 11 (13th October 2022) - Carrier, Coralie; Habibi, Azza; Agarande, Michelle; Augeray, Celine; Bourles, Didier; Maro, Denis; Benedetti, Lucilla
Abstract : Correction for 'Mass-shift mode to quantify low level 129 I in environmental samples by ICP-MS/MS' by Coralie Carrier et al., J. Anal. At. Spectrom., 2022, 37, 1309–1317, ; https://doi.org/10.1039/D2JA00128D .